Media Tactics and Taste: Organising the Southern Labour Movement at Highlander Folk School, 1938-1946 - Durham, Frank (Javnost-The Public, 2005)
Between 1938-1946, the Highlander Folk School’s socialist faculty fostered a collective identity formation process among union workers and officials by teaching these students to write autobiographical statements of purpose, dramatics, music, and journalism. This historical essay considers the role of media education at Highlander in the labour movement that emerged in the American South just prior to World War II. Based on archival materials, it asks why the interpersonal media of labour theatre and music were more popular and effective as organizing tactics among the labour students at Highlander than the mass medium of journalism. Within a discussion of social movement theories that considers how and why social movement participants act as they do, the argument presented here suggests that American labour movement activists acted on the basis of their prior experiences and affective connections to those contexts.